A GBD 2021 study of Alzheimer’s disease and other dementias attributable to metabolic risk factors and forecasts to 2045 in China - Zhu, Meng’en; Bi, Zhimin; Zhou, Shaoqiong; Li, Wei (Frontiers in Public Health, 2025)
Background and aimsHigh fasting plasma glucose (FPG) and body mass index (BMI) are recognized as significant metabolic risk factors for Alzheimer’s disease (AD) and other dementias. This study assesses the burden of AD and other dementias attributable to these risks in China using Global Burden of Disease (GBD) 2021 data.MethodsWe estimated deaths, disability-adjusted life-years (DALYs), years lived with disability (YLDs), and age-standardized rates of mortality (ASMR), DALYs (ASDR), and YLDs (ASYR) by age and sex. Temporal trends were analyzed via the average annual percentage change (AAPC), and Bayesian age-period-cohort (BAPC) models were applied to evaluate the effects of age, period, and cohort.ResultsIn 2021, China recorded 76,239.36 deaths (95% UI: 2,528.26–259,225.86) from AD and other dementias due to metabolic risks, a 4.7-fold increase from 1990. Females experienced more metabolic risk-related deaths [51,844.08 (95% UI, 1,457.44, 177,037.05)] than males. The ASMR, ASDR, and ASYR showed continuous increases from 1990 to 2021, with AAPC values of 1.03, 1.31, and 1.98%, respectively. A significant increasing trend was observed across age groups from 40 to 95 years, with percentages above 0. Females presented relatively higher risks than males after 1997–2001 and within the birth cohort groups of 1957–1966. The disease burden due to HBMI is expected to rise, while that due to HFPG will decline, notable sex will persist until 2045.ConclusionMonitoring trends is crucial for interventions to reduce the future disease burden, particularly among women and older populations in China, to guide healthcare resource allocation effectively.